Utolsó előadás . The Last Performance - Zámborszki, Ákos (Golden Root Film, 2010)
Verzio FF Circo Soluna is a 20-year-old traveling circus run by the German Brender family: two parents and three children. They travel in wagons from village to village around Europe bringing joy and love to people living in the remotest rural areas. These nomads of the 21st century live, eat and sleep in their wagons in a freedom that many of us only dream of. At the end of the summer, their last show marks the beginning of their long winter break when they need to move on to areas where there is grass and water for the horses. This particular performance, however, is special for another reason as well.